Antarctic biogeography revisited: updating the Antarctic Conservation Biogeographic Regions. Issue 8 (15th June 2016) - Terauds, Aleks; Lee, Jasmine R.
Abstract: The Antarctic Conservation Biogeographic Regions (ACBRs), originally proposed in 2012, are now established as an important tool in Antarctic science, conservation, management and policy. Here, we provide a revised version of the ACBRs, reflecting updates in underlying spatial layers, together with the results of new analyses justifying the inclusion of a 16th bioregion. This updated version now covers all ice‐free areas of Antarctica and is publicly available through the Australian Antarctic Data Centre. In light of the interest in the ACBRs across a variety of research fields, we also provide a new set of summary statistics for the updated spatial layer, including landscape metrics, climate data, protected area coverage and an overview of human activity. The updated ACBRs represent a contemporary, practical and evidence‐based foundation for understanding, conserving and managing Antarctic biodiversity at a continental scale.